Электрические явления при облучении полимеров - Тютнев А. П. Андрей Павлович; Ванников А. В. Анатолий Вениаминович; Мингалеев Г. С. Гумар Салихович; Саенко В. С. Владимир Степанович (Москва, Энергоатомиздат, 1985)
Авт. указаны на обороте тит. л.